pH of the luminal surface of the gastrointestinal mucosa of baby alpacas during the first weeks of age - Vásquez C., María (2012)
The objective of this study was to determine the pH in the luminal mucosa of the gastric compartments and intestinal segments during the first 45 postnatal days of age in the alpaca (Vicugna pacos). Thirty three alpacas from birth to 45 days of age were distributed in seven age groups. The animals proceeded from the Puno and Cusco departments of Peru. The pH was measured using a 826 pH mobile meter with a special flat electrode for membranes. Animals were slaughtered and the gastrointestinal tract was divided in 13 segments. An 8-cm length opening was done in each segment and pH was directly measured over the mucosa. The pH of compartments 1, 2 and 3 (segment abomasum) was lower at birth (p<0.05), increased during the first week and kept constant until 45 days of age. The pH in the intestinal segments was constant in all age groups, but there was a slight tendency to acidity in the small intestine and a tendency to neutrality in the large intestine. This suggests that alpacas of these ages have homeostatic mechanisms for maintaining constant the pH of the microclimate in the gastrointestinal tract despite the change of feeds during the first phase of postnatal life.